Grebeg Mantra Memetri of Wonosari Residents Village, Tutur District: A Semiotic Studies - Devito Andharu; Wahyu Widayati; M Reza Ishadi Fadillah; Rommel Utungga Pasopati (Journal Corner of Education, Linguistics, and Literature, 2023)
This study aims to find the meaning of the mantra sign in the tradition of Grebeg Memetri. This research uses a qualitative approach. The data source in this study is the spell of slaughtering a cow's head in the Grebeg Memetri tradition. The data collection technique was carried out by primary observation of the Grebeg Memetri tradition done by residents of Wonosari village in Tutur district. The observation is done by conducting audio-visual and picture recordings using tape recorders and handy cams as well as exploratory interviews related to the Grebeg Memetri tradition done by residents of Wonosari village in Tutur district. Based on the results of the analysis, there are five code systems, namely the HER code, which indicates the existence of an enigma in it; the proaretic code (ACT), which regulates the flow of a story or narrative and guarantees that the text read is a story, the semik code (SEME) that makes use of cues, clues, or flashes of meaning elicited by certain markers, cultural code (REF) as markers that refer to a set of references or general knowledge, and symbolic code (SYM) that refers to a set of references or general knowledge that supports the text.